Strategic Interactive Instruction for Improving Deaf Students’ English Composition in Indonesian Special Schools - Khoirul Huda; Rodli Rodli; Daniar Shofeny; Buyun Khulel; Syifa' Khuriyatuz Zahro; Anita Dwi Hapsari (PT. Global Research Collaboration, 2026)
Classroom-based evidence on Strategic Interactive Writing Instruction (SIWI) in Indonesian special-school contexts remains limited, despite the urgent need for accessible English composition instruction for deaf students. This qualitative case study examines how SIWI supports English writing among seventh-grade deaf students in an Indonesian special school. Data were collected through semi-structured interviews with two English teachers, classroom observations, and document analysis of student writing samples and instructional materials. Reflexive thematic analysis identified three connected patterns. First, teachers implemented SIWI through visual scaffolding, gestures, board modeling, guided vocabulary work, and shared text construction. Second, students became more willing to participate in writing activities when English words were linked to visible meanings and immediate feedback. Third, student progress appeared strongest in vocabulary, formulaic expressions, and simple sentence frames, while paragraph organization, genre control, and independent revision remained limited. The study contributes classroom-level evidence on locally adapted SIWI practice in an Indonesian SLB context. It suggests that SIWI can make English writing more accessible for deaf learners when teachers combine language access, interaction, and explicit metalinguistic mediation. Further instruction should strengthen systematic writing portfolios, genre-based tasks, and rubric-guided assessment.